Ghanaian nurses' and midwives' perspectives on technology adoption in nursing and midwifery education - Charles Ampong Adjei; Samuel Adjorlolo; Josephine Kyei; Lillian Akorfa Ohene; Gladys Dzansi; Angela Kwartemaa Acheampong; Isabella Naana Akyaa Asante; Philomena Woolley; Felix Nyante; Lydia Aziato (Wiley, 2023)
Abstract Aim The purpose of this study was to explore the perceived benefits and challenges of online distance education and computer‐based testing (CBT) among registered nurses and midwives in a sample of government‐owned health facilities and health training institutions in Ghana. Design Exploratory descriptive qualitative design. Methods Individual semi‐structured interviews were conducted with 45 participants (i.e. 25 nurses and 20 midwives). The data were manually processed and analysed using Braun and Clarke's thematic analysis approach (November 2019‐February 2020). Results Nurses and midwives prefer online distance education for three reasons: convenience, cost‐effectiveness and learning centre proximity to the workplace. The course schedule's flexibility allowed participants to work and study simultaneously. Others acknowledged online distance education as a viable option for overcoming the challenges of obtaining study leave. However, the lack of recognition of certificates by some employers, poor Internet connectivity and perceived excessive course load were noted as deterrents. Regarding the CBT, many of the participants said that it was useful. Among the advantages of CBT are: (1) a decrease in examination malpractices, (2) a decrease in examination costs and (3) a rise in students' interest in information, communication and technology (ICT). This finding emphasizes the necessity of integrating ICT into nursing and midwifery education and examinations, as well as maximizing its benefits.